2016
DOI: 10.1016/j.cmet.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Function of GALNT2 Lowers High-Density Lipoproteins in Humans, Nonhuman Primates, and Rodents

Abstract: Summary Human genetics studies have implicated GALNT2, encoding GalNAc-T2, as a novel regulator of high-density lipoprotein cholesterol (HDL-C) metabolism, but the mechanisms relating GALNT2 to HDL-C remain unclear. We investigated the impact of homozygous GALNT2 deficiency on HDL-C in humans and mammalian models. We identified two humans homozygous for loss-of-function mutations in GALNT2 who demonstrated low HDL-C. We also found that GALNT2 loss-of-function in mice, rats, and nonhuman primates decreased HDL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
150
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 114 publications
(157 citation statements)
references
References 38 publications
7
150
0
Order By: Relevance
“…Genetic deficiency in GALNT11 has not been identified so far in man and it is predicted to be extremely rare if occurring (34), but GALNT11 has been identified as a GWAS candidate gene for chronic kidney decline (46). The GWAS signal for chronic kidney decline resides in intron one of the GALNT11 gene, suggesting that the genetic predisposition is a result of altered gene regulation, similar to what has been established for the role of GALNT2 in dyslipidemia (19,47). Our study did not directly address the functional role of Oglycans on other LDLR-related proteins including LRP2, however, GalNAc-T11 is highly expressed in proximal tubules of the kidney and LRP2 is the major endocytic receptor responsible for reabsorbtion of proteins from the glomerular filtrate (21, 48).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Genetic deficiency in GALNT11 has not been identified so far in man and it is predicted to be extremely rare if occurring (34), but GALNT11 has been identified as a GWAS candidate gene for chronic kidney decline (46). The GWAS signal for chronic kidney decline resides in intron one of the GALNT11 gene, suggesting that the genetic predisposition is a result of altered gene regulation, similar to what has been established for the role of GALNT2 in dyslipidemia (19,47). Our study did not directly address the functional role of Oglycans on other LDLR-related proteins including LRP2, however, GalNAc-T11 is highly expressed in proximal tubules of the kidney and LRP2 is the major endocytic receptor responsible for reabsorbtion of proteins from the glomerular filtrate (21, 48).…”
Section: Discussionmentioning
confidence: 94%
“…We previously did confirm some of the LDLR, VLDLR and LRP1 sites in WT CHO cells (18), as well as in rat liver and human plasma (19) (Fig. 1, labeled 2,3 and Suppl.…”
Section: O-glycosites In the Linker Regions Of Class A Repeats Of Ldlmentioning
confidence: 91%
See 2 more Smart Citations
“…Of the four ADAMS analyzed, we found that ADAM17 cleaved peptide II at 52 P2L 53 and that this was inhibited by GalNAc-T2 glycosylation ( Fig. 2A).…”
Section: Site-specific O-glycosylation By Galnac-t2 Modulates the Inmentioning
confidence: 99%